15N natural abundance of grass tissue might be linked to Biological Nitrification Inhibition activity in soil - CGIAR Research Program on Climate Change, Agriculture and Food Security (2018)
The method described here can serve as an indicator of the extent of NO3 leakiness for BNI field evaluations over the years, if combined with other BNI indicators like the abundance and activity of soil nitrifiers under the given conditions set out above.